PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK YANG TERDAFTAR PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BEI PERIODE 2015-2019 - widiyastuti, tri; Siti Nurlaela; Yuli Chomsatu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the influence of profitability, company size and leverageon corporate tax aggressiveness. The population in this study is plastics andpackaging companies listed on the Indonesia Stock Exchange for the period 2015-2019. The company samples as many as 13 (thirteen companies) companies, as manyas 5 (four) years of research period and this research sample using purposivesampling techniques, the number of research samples as many as 60 samples. Theresults of the first hypothesis test explain that profitability affects the aggressivenessof taxes on companies and packaging.. The results of hypothesis 2 testing show thatthe size of the company affects the aggressiveness of taxes. The results of hypothesis3 testing show that leverage has no effect on tax aggressiveness.